2021
DOI: 10.1177/0095244320988163
|View full text |Cite
|
Sign up to set email alerts
|

TG and DSC as tools to analyse the thermal behaviour of EVA copolymers

Abstract: This paper analyses the thermal behaviour of six EVA copolymers supplied by REPSOL Company. In relation to crystallization and melting temperatures, both of them decrease when the vinyl acetate percentage increases, in agreement with the fact that polyethylene is a semi-crystalline material, whereas polyvinylacetate is an amorphous polymer. Actually, when the vinyl acetate percentage reaches 30%, the copolymer is practically amorphous. The non-isothermal crystallization was modelled with the modified Avrami mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The EVA-0 and NAEDS-0 exothermic peaks near 70°C corresponded to the ethylene crystallization in the EVA molecular chain. 39 The heat-absorbing peak near 80°C was attributed to the resin melting. The NAEDS-20 resin exothermic peak disappeared near 70°C, which may be because the nano alumina was not well dispersed in the EVA molecular chain, hindering the molecular chain movement and affecting the crystallization in the EVA ethylene segment.…”
Section: Resultsmentioning
confidence: 99%
“…The EVA-0 and NAEDS-0 exothermic peaks near 70°C corresponded to the ethylene crystallization in the EVA molecular chain. 39 The heat-absorbing peak near 80°C was attributed to the resin melting. The NAEDS-20 resin exothermic peak disappeared near 70°C, which may be because the nano alumina was not well dispersed in the EVA molecular chain, hindering the molecular chain movement and affecting the crystallization in the EVA ethylene segment.…”
Section: Resultsmentioning
confidence: 99%
“…[32] A recent study demonstrated that the higher the VA content, the more the first weight loss. [33] In POE and TPO, TGA underwent a long thermal stability phase, followed by a single-stage decomposition at 436 and 444 °C, respectively, associated with polymer main chain loss. [34] The crystallization and melting behaviors are depicted in DSC curves (Figure 1b).…”
Section: Materials Properties Analysis Of Different Encapsulantsmentioning
confidence: 99%